Group I metabotropic glutamate receptors bind to protein phosphatase 1C: Mapping and modeling of interacting sequences. - Croci, Cristina; Sticht, Heinrich; Brandstätter, Johann Helmut; Enz, Ralf (Journal of Biological Chemistry, 2003)
The modulation of neurotransmitter receptors by kinases and phosphatases represents a key mechanism in controlling synaptic signal transduction. However, molecular determinants involved in the specific targeting and interactions of these enzymes are largely unknown. Here, we identified both catalytic γ-isoforms of protein phosphatase 1C (PP1γ1 and PP1γ2) as binding partners of the group I metabotropic glutamate receptors type 1a, 5a, and 5b in yeast cells and pull-down assays, using recombinant and native protein preparations. The tissue distribution of interacting proteins was compared, and protein phosphatase 1C was detected in dendrites of retinal bipolar cells expressing the respective interacting glutamate receptors. We mapped interacting domains within binding partners and identified five amino acids in the intracellular C termini of the metabotropic glutamate receptors type 1a, 5a, 5b, and 7b being both necessary and sufficient to bind protein phosphatase 1C. Furthermore, we show a dose-dependent competition of these C termini in binding the enzyme. Based on our data, we investigated the structure of the identified amino acids bound to protein phosphatase 1C by homology-based molecular modeling. In summary, these results provide a molecular description of the interaction between protein phosphatase 1C and metabotropic glutamate receptors and thereby increase our understanding of glutamatergic signal transduction.
UnivIS-Import:2015-04-14:Pub.2003.med.IB.profes_1.groupi